GAMBARAN KUALITAS HIDUP CARE GIVER PASIEN LANJUT USIA DI RSUP SANGLAH - Auryn, Sylvester; Diniari, Ni Ketut Sri (E-Jurnal Medika Udayana; Vol 5 No 5 (2016): E-jurnal medika udayana, 2016)
Increased life expectancy of the population has occurred in the world and Indonesia, which are associated with aging and morbidity. Keeping and caring for a loved one can provide benefits but also provide a burden at the same time which will affect the quality of life of an individual. The purpose of this study was to determine the quality of life of elderly patients care giver at Sanglah Hospital. This study is a cross-sectional descriptive study with data collection conducted on March 1, 2016 - March 7, 2016. From a total of 30 respondents who are caregivers of elderly patients, it is obtained that the majority were female sex (60%) with the largest age group is 20-39 years (50%). Most respondents (63.3%) is the son or daughter of the patient and are still working daily (73.3%). Subjectively, the majority (56.7%) of caregivers think they got a bad quality of life, while in terms of health majority (53.3%) of the caregivers satisfied with their own health. Objectively, as many as 20 people (66.7%) of caregiver already has a relatively good quality of life and 10 people (33.3%) classified as bad in general with the average of 55.77.  More attention is required and also the role of the family to the care giver of elderly patients that will be better given by a multidisciplinary team.
Keywords: quality of life, caregiver, elderly patients